1998
DOI: 10.1071/mf94161
|View full text |Cite
|
Sign up to set email alerts
|

Flow variability and the ecology of large rivers

Abstract: Ecological processes in large rivers are controlled by their flow variability. However, it is difficult to find measures of hydrological variability that characterize groups of rivers and can also be used to generate hypotheses about their ecology. Multivariate analyses of the hydrographs of 52 rivers worldwide revealed distinctive patterns of flow variability that were often correlated with climate. For example, there were groups of rivers that corresponded broadly with ‘tropical’ and ‘dryland’ climates. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
501
0
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 599 publications
(509 citation statements)
references
References 0 publications
5
501
0
3
Order By: Relevance
“…Prior to analysis, screening of raw data ensured a benchmark period of 20-years (1980 -1999) A total of 201 hydrological indices used in 15 previously published articles were used in our analysis (Hughes and James, 1989;Poff and Ward, 1989;Richards, 1989;Biggs, 1990; Jowett and Duncan, 1990; Poff, 1996;Richter et al, 1996;Clausen and Biggs, 1997;Richter et al, 1997;Puckridge et al, 1998;Richter et al, 1998;Clausen and Biggs, 2000;Wood et al, 2000;Wood et al, 2001). For brevity, Appendix 1 lists those variables identified by the PCA method and/or utilised in regression models in this paper (for full details of all candidate variables see Monk et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Prior to analysis, screening of raw data ensured a benchmark period of 20-years (1980 -1999) A total of 201 hydrological indices used in 15 previously published articles were used in our analysis (Hughes and James, 1989;Poff and Ward, 1989;Richards, 1989;Biggs, 1990; Jowett and Duncan, 1990; Poff, 1996;Richter et al, 1996;Clausen and Biggs, 1997;Richter et al, 1997;Puckridge et al, 1998;Richter et al, 1998;Clausen and Biggs, 2000;Wood et al, 2000;Wood et al, 2001). For brevity, Appendix 1 lists those variables identified by the PCA method and/or utilised in regression models in this paper (for full details of all candidate variables see Monk et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Ecologically, water is the most limiting factor for plant growth in arid environments. The spatio-temporal dynamics of vegetation are, therefore, largely determined by available water [68][69][70][71][72][73]. Not surprisingly, biotic diversity is concentrated in riparian areas [74,75].…”
Section: Figurementioning
confidence: 99%
“…The 'ecologically-relevant' hydrological variables were identified from previous research reported within 15 hydrological and ecological journal papers (see Appendix I, Hughes and James, 1989;Poff and Ward, 1989;Richards, 1989;Biggs, 1990;Jowett and Duncan, 1990;Poff, 1996;Richter, et al, 1996;Clausen and Biggs, 1997;Puckridge, et al, 1998;Richter, et al, 1998;Clausen and Biggs, 2000;Clausen, et al, 2000;Wood, et al, 2000;Wood, et al, 2001). Flow variables were assigned to one of five hydrological regime facets, as originally proposed in the Indicators of Hydrologic Alteration methodology (Richter, et al, 1996) and its derivatives (Poff, et al, 1997;Olden and Poff, 2003).…”
Section: Correlation and Regression Analysismentioning
confidence: 99%